Pursuit of Fairness: Human Rights and Social Justice in Indonesia's Legal Landscape - Iristian, Yovan (Journal of Progressive Law and Legal Studies, 2024)
This study thoroughly examines how human rights protection and the pursuit of justice intersect within the framework of Indonesia. Considering the nature of society, this research critically analyzes the complex challenges that hinder equal rights for all citizens. The focus is on exploring the mechanisms embedded in the Indonesian system that aim to safeguard and advocate for fairness. This study delves deeply into addressing and rectifying social justice issues within this context. Using a methodology that combines analysis with empirical research, this research uncovers the intricate complexities and contradictions in the legal landscape. Tracing the evolution of jurisprudence and legislative efforts sheds light on milestones and obstacles toward fairness and equity. The objective of this research is to contribute insights to discussions regarding human rights and social justice offering a nuanced understanding of both challenges faced and advancements made within Indonesia's legal system. Ultimately it aspires to provide recommendations to policymakers, legal professionals, and stakeholders to create an environment that unwaveringly upholds human rights while fostering social justice for all segments of Indonesian society.